Tajikistan : Early Childhood Development - World Bank (Washington, DC, 2013)
This report presents an analysis of the Early Childhood Development (ECD) programs and policies which affect young children in Tajikistan. This report is part of a series of reports prepared by the World Bank using the Systems Approach for Better Education Results (SABER)-ECD framework. Tajikistan has a population of 7.76 million people, of which 35 percent are below the age of 15. Unlike some countries in the region, Tajikistan has a positive population growth rate. SABER-ECD collects, analyzes and disseminates comprehensive information on ECD policies around the world. In each participating country, extensive multi- sectoral information is collected on ECD policies and programs through a desk review of available government documents, data and literature, and interviews with a range of ECD stakeholders, including government officials, service providers, civil society, development partners and scholars. SABER-ECD identifies three core policy goals that countries should address to ensure optimal ECD outcomes: establishing an enabling environment, implementing widely and monitoring and assuring quality. Improving ECD requires an integrated approach to address all three goals. Tajikistan has taken steps to develop and adopt national laws and regulations that promote appropriate dietary consumption by pregnant women and young children.